The Role of Glucosamine Chondrotin Sulfate in the Treatment of Osteoarthritis of Knee - AlMukhtar, Sadeq A.; Al-Muktar, Sinan (AL-Kindy College Medical Journal, 2013)
Background: Osteoarthritis (OA) currently seemsinevitable and unavoidable for a large swath of thepopulation .its etiology relates to a strong ,butcomplex ,non mendelian genetic basis ,combinedwith mechanical and metabolic factors that causemolecular alterations the end results of whichaffect the whole joint .Glucosamine andchondrotin sulfate alone or in combination may beof benefit to a subgroup of individuals who haveknee pain due to OA.Glucosamine has been shown to alter cartiage turnover in patients with OA undergoing physicaltrainingAim of the study: To find the validity ofglucosamine chondrotin sulfate in treatment ofgrade 1 and 2 OA.Methods: the sample of 280 patients (418 knee)were divided in to two groups , group A (132patient) treated by classical methods byglucosamine chondrotin sulfate for one year. Forboth groups different parameters were usedincluding pain stiffness effusion crepitus and genuvarum and different radiological findings and weused MRI for evaluation pre and post treatmentResult: Female/ male ratio was 2.89 the highestage group was ( 60-69) year regarding the clinicalpresentation of patients the commonest clinicalpresentation were pain and stiffness and the MRIfinding including bone marrow edema shows goodindicator for response to treatment .Conclusion: Pain ,stiffness and crepitus werecommon presentation of OARelief of painandstiffness were related to decrease of effusionand bone marrow edema which is the result ofusing nonsteroidal anti-inflammatory drugs withglucosamine chondroitin sulfate more than whennon steroidal anti- inflammatory drugs alone.